Development and characterization of NILK-2301, a novel CEACAM5xCD3 κλ bispecific antibody for immunotherapy of CEACAM5-expressing cancers - Anja Seckinger; Sara Majocchi; Valéry Moine; Lise Nouveau; Hoang Ngoc; Bruno Daubeuf; Ulla Ravn; Nicolas Pleche; Sebastien Calloud; Lucile Broyer; Laura Cons; Adeline Lesnier; et al. (Journal of Hematology & Oncology, 2023)
Abstract Background T-cell retargeting to eliminate CEACAM5-expressing cancer cells via CEACAM5xCD3 bispecific antibodies (BsAbs) showed limited clinical activity so far, mostly due to insufficient T-cell activation, dose-limiting toxicities, and formation of anti-drug antibodies (ADA). Methods We present here the generation and preclinical development of NILK-2301, a BsAb composed of a common heavy chain and two different light chains, one kappa and one lambda, determining specificity (so-called κλ body format). Results NILK-2301 binds CD3ɛ on T-cells with its lambda light chain arm with an affinity of ≈100 nM, and the CEACAM5 A2 domain on tumor cells by its kappa light chain arm with an affinity of ≈5 nM. FcγR-binding is abrogated by the “LALAPA” mutation (Leu234Ala, Leu235Ala, Pro329Ala). NILK-2301 induced T-cell activation, proliferation, cytokine release, and T-cell dependent cellular cytotoxicity of CEACAM5-positive tumor cell lines (5/5 colorectal, 2/2 gastric, 2/2 lung), e.g., SK-CO-1 (E max = 89%), MKN-45 (E max = 84%), and H2122 (E max = 97%), with EC50 ranging from 0.02 to 0.14 nM. NILK-2301 binds neither to CEACAM5-negative or primary colon epithelial cells nor to other CEACAM family members. NILK-2301 alone or in combination with checkpoint inhibition showed activity in organotypic tumor tissue slices and colorectal cancer organoid models. In vivo, NILK-2301 at 10 mg/kg significantly delayed tumor progression in colon- and a pancreatic adenocarcinoma model. Single-dose pharmacokinetics (PK) and tolerability in cynomolgus monkeys at 0.5 or 10 mg/kg intravenously or 20 mg subcutaneously showed dose-proportional PK, bioavailability ≈100%, and a projected half-life in humans of 13.1 days. NILK-2301 was well-tolerated. Data were confirmed in human FcRn TG32 mice. Conclusions In summary, NILK-2301 combines promising preclinical activity and safety with lower probability of ADA-generation due to its format compared to other molecules and is scheduled to enter clinical testing at the end of 2023.